Methodological approaches to the digital infrastructure function analysis - Vavilina, Alla Vladimirovna (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. The article presents a methodology for studying the essence of digital infrastructure as an element of national economy and a source of its technical and technological development. Understanding the essence of digital infrastructure involves analyzing its functions: organizing, generating, transforming. Theoretical analysis. Digital infrastructure as an element of the reproductive structure, moving within the framework of general trends in economic development, is considered as a condition for the vital activity of innovative entities, a sphere of knowledge and technology generation, a way of their transformation into the economic space where they are applied. The functional qualities that express the main thing in the content of digital infrastructure as an economic phenomenon are identified, a justification of its properties is given, an analysis of the digital infrastructure functions is carried out, the movement of capital value is considered, accompanied by a number of important economic processes: a change in capital forms; accumulation of technical and technological resources that provide major scientific and technological breakthroughs in the field of new materials, energy sources, production equipment, in the field of building a new technological basis for the country. Results. The transformative potential of digital infrastructure is revealed through the action of special lines of force – factors that influence the reproductive sphere at the main points of material production development, information space, social sphere, and exchange sphere, formed within the framework of separate but interconnected “factor fields”.